Sosialisasi Kondisi Fisik Bola Basket Pada Siswa Ekstrakurikuler di SMA Negeri 1 Kuantan Hilir Kabupaten Kuantan Singingi - Candra, Oki; Dupri, Dupri; Gazali, Novri; Khairullazi, Khairullazi; Oktari, Annisa (Community Education Engagement Journal, 2019)
This community service is motivated by the lack of knowledge of basketball coaches and extracurricular students in knowing the physical condition of the physical condition. As for the participants in the workshop on the socialization of physical conditions in extracurricular basketball students, there were 35 extracurricular students and 1 basketball coach in SMA 1, Kuantan Hilir, Kuantan Singingi Regency. This activity was carried out on 3-4 August 2019 which took place in the classroom and basketball court at SMA Negeri 1 Kuantan Hilir. The results on community service were that first basketball extracurricular students began to understand the form of exercises and the steps to perform physical conditions that were good and correct in theory and practice. The two results seen in the coach can provide scientific knowledge of physical conditions, especially basketball, starting from endurance, speed, strength, coordination and flexibility and so on, can apply in a structured and planned manner. Of all the community service activities that have been carried out at SMA Negeri 1 Kuantan Hilir, Kuantan Singingi Regency, it can be seen that basketball extracurricular students are very enthusiastic about this activity and the students and instructor teachers ask us to continue in the future.